Optimalisasi pembelajaran geometri berbasis budaya dengan microlearning dan Padlet di MTs Negeri Ambon - Riaddin, Dinar; Assagaf, Gamar; Waru, Misveria Villa (PYTHAGORAS : Jurnal Program Studi Pendidikan Matematika, 2025)
Geometry education is often considered difficult by students because of its complex concepts. This study aims to explore the effectiveness of using microlearning and Padlet in culture-based geometry learning at MTs Negeri Ambon. This study used a pretest-posttest experimental design with a control group. This study used two VIII classes as samples, where one class was an experimental class and the rest were control classes. The results showed an increase in the average value of geometry understanding in the experimental class, although it was not significantly different. The magnitude of the effect (r = 0.163) showed a small effect but showed the positive potential of using this technology in geometry learning. This study emphasizes the importance of integrating technology and local culture into the mathematics curriculum to improve students' understanding.